Molecular detection of Middle East Respiratory Syndrome Coronavirus (MERS-CoV) in Tunisian dromedary camels (Camelus dromedarius) - Z. AZAOUZI (Revue Marocaine des Sciences Agronomiques et Vétérinaires, 2018)
Middle East Respiratory Syndrome Coronavirus (MERS-CoV) was identified in humans in 2012. Dromedary camels were considered as the major reservoir of the virus throw several studies. Tunisian dromedary camels were implicated in a serological survey and a seropositivity reaching 100% was observed among some of them. Therefore, more investigations are necessary to look for the current infection situation. In this study, we aimed to detect the MERS-CoV virus in our camels by molecular technics. Blood and nasal swabs samples from 64 dromedary camels from 4 Tunisian provinces were collected during June 2014 and April 2015. All the animals tested negative by real time reverse transcriptase–polymerase chain reaction assay (RT-PCR). These findings could not confirm the absence of MERS-CoV active shading among the Tunisian camel population and more researches should be carried on to survey dromedary camels in Tunisia and its neighboring countries.